English Language Preservice Teachers’ Identity Construction Within Academic and Other Communities - Julia Posada-Ortiz (Profile: Issues in Teachers' Professional Development)
This article reports on a doctoral research that sought to unveil the identities present in the communities to which four English as a foreign language preservice teachers belong. The study was carried out with a decolonial perspective that included an interepistemic dialogue among narrative inquiry, narrative pedagogy, and the indigenous research paradigm. The main instrument of data collection was autobiographies. The participants and the researcher analysed data jointly. The findings indicate that the preservice teachers’ identity construction is mutable and not essentialised. Mutable as it changes over time and not essentialised since it involves social, cultural, and personal dimensions.